Relevansi Etika Politik Peter Ludwig Berger bagi Pembangunan Pariwisata Premium di Labuan Bajo, Nusa Tenggara Timur - Solosumantro, Heribertus (Bina Nusantara University, 2025)
Abstract- The history of development in a reality of human life occupies a space and context of fundamental change. The space and context of change absorb the paradoxical dimensions of human life. Accommodation of interests that dominate position, authority, collective policies, and development values ​​also reduce the identity of development. This can be seen in the development of tourism in the premium city of Labuan Bajo. This paper aims to explain the political ethics of development as a concrete step in seeing, reflecting, and making decisions about the collective development of a society. A review of political ethics in development is an effort to understand the reality of injustice and discrimination of the morality of the rights of poor and oppressed minority communities. The results and discussion show that the reality of people's lives that live in the collective imagination of building the world of tourism development in Labuan Bajo also invites critical analytical reviews in the idealism of political development. Two main points found that as far as the concept of calculus of pain and calculus of meaning inhabits a political ethics of development, society gets an invitation to be involved in critical analysis and ethical sensitivity of collective development. Peter L. Berger is of the view that to become a whole human being certainly requires reflection as well as action. Keywords: Political ethics, Berger, Development, calculus of pain, calculus of meaning, Labuan Bajo. Abstrak Sejarah pembangunan dalam suatu realitas kehidupan manusia menempati ruang dan konteks perubahan yang fundamental. Ruang dan konteks perubahan itu menyerap dimensi-dimensi kehidupan manusia yang paradoksal. Akomodasi kepentingan-kepentingan yang menguasai kedudukan, wewenang, kebijakan kolektif, dan nilai pembangunan turut mereduksi identitas pembangunan. Hal ini terlihat dalam pembangunan pariwisata kota premium Labuan Bajo. Tulisan ini hendak menjelaskan etika politik pembangunan sebagai langkah konkrit dalam melihat, merefleksikan, dan mengambil keputusan pembangunan kolektif suatu masyarakat. Tinjauan etika politik dalam pembangunan adalah usaha memahami realitas ketidakadilan dan diskriminasi moralitas hak-hak minoritas masyarakat miskin dan tertindas. Hasil dan pembahasan menunjukan bahwa realitas kehidupan masyarakat yang tinggal dalam imajinasi kolektif membangun dunia pembangunan pariwisata di Labuan Bajo juga mengundang tinjauan kritis analitis dalam idealisme politik pembangunan. Dua poin utama yang ditemukan bahwa sejauh konsep calculus of pain dan calculus of meaning mendiami suatu etika politik pembangunan, masyarakat mendapatkan undangan keterlibatan dalam analisis kritis dan kepekaan etis suatu pembangunan kolektif. Peter L. Berger berpandangan bahwa untuk menjadi manusia seutuhnya tentunya membutuhkan refleksi sekaligus tindakan. Kata kunci: Etika politik, Berger, pembangunan, calculus of pain, calculus of meaning, Labuan Bajo.